2005
DOI: 10.1080/15287390590967432
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Status in Patients with Alcohol Dependence: A Clinical Study in Taiwan

Abstract: The aim of this study is to examine the relationship between alcohol dependence and oxidative status. The biochemical parameters and antioxidants status were measured among 28 patients with alcohol dependence. Nineteen healthy persons without drinking problem were recruited as the control subjects. The activities of aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma glutamyltransferase (gamma-GT), and levels of cholesterol, triglyceride (TG), and uric acid were significantly increased in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 39 publications
6
32
0
1
Order By: Relevance
“…This was demonstrated for the antioxidant enzymes such as SOD, GPX and CAT (12,19,20), but also for the classic antioxidants such as glutathione (21). Also, the lipid peroxidation processes, as evaluated through the various levels of thiobarbituric acid reactive substances (TBARS), were reported to be significantly decreased in the CSF or blood of chronic alcohol consumers (16,22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated for the antioxidant enzymes such as SOD, GPX and CAT (12,19,20), but also for the classic antioxidants such as glutathione (21). Also, the lipid peroxidation processes, as evaluated through the various levels of thiobarbituric acid reactive substances (TBARS), were reported to be significantly decreased in the CSF or blood of chronic alcohol consumers (16,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Also, for MDA, the main marker of the lipid peroxidation processes, while several studies have found elevated levels in the serum of patients undergoing alcohol withdrawal (20,22,29), there are also reports describing clear reductions in the various markers lipid peroxidation following alcohol withdrawal (12,30).…”
Section: Discussionmentioning
confidence: 99%
“…A solid body of literature exists in support of the association between oxidative stress and common drugs of abuse, including nicotine (Petruzzelli et al, 2000), alcohol (Peng et al, 2005), cannabis (Sarafian et al, 1999), heroin (Pan et al, 2005), cocaine and amphetamines (Frey et al, 2006c). Although their precise roles are yet to be fully understood, oxidative mechanisms have been proposed to mediate both the processes of drug addiction and toxicity (Kovacic, 2005;Kovacic and Cooksy, 2005), and antioxidants may thus have therapeutic potential in the management of these conditions.…”
Section: Substance Abusementioning
confidence: 99%
“…(24) However, many studies have also shown decreased levels of SOD in blood cells of alcoholic. (13), (25) This discrepancy between various studies may be due to the different methods used for estimation of SOD and needs further clarification. The auto oxidation assays of SOD have many limitations giving varied levels even in normal subjects.…”
Section: Resultsmentioning
confidence: 99%
“…There have not been much clinical studies of oxidative stress in apparently healthy alcoholics after adjusting for the effect of other confounders such as smoking and many of them have produced conflicting results. (11), (12), (13) Meanwhile, some recent studies have shown increased oxidative stress during the alcohol withdrawal state also. (14), (15), (16) As this was found to correlate with glutamatergic excitotoxicity of the withdrawal state, it was put forth as a possible mechanism mediating the symptoms of alcohol withdrawal.…”
Section: Introductionmentioning
confidence: 99%